A pauta da seca na Tv Sergipe : uma análise da cobertura jornalística à luz do jornalismo de soluções - Farias, Camila Gabrielle Oliveira de (2022)
The Northeast region is composed of 9 states in Brazil, which together make up practically the entire semiarid region. With characteristics such as irregular rainfall, the site can also be affected by periods of drought; a type of recurring agenda in the television media. Based on a bibliographic survey on the subject, this work investigated how local television journalism, specifically on TV Sergipe - which is a television station affiliated with Rede Globo, covered the drought between the years 2017 to 2019, identifying whether public policies, techniques of coexistence with the drought or actions to combat deforestation of the caatinga in the state were addressed. The objective was to verify if the solutions presented by TV Sergipe to the drought issue were within the perspective focused on solutions journalism. The temporal cut was chosen because it was after the severe drought that hit parts of the region. The state of Sergipe was chosen for this analysis because more than 50% of its territory is part of the semi-arid region, in addition to the cultural identification by the research author. As a method, content analysis was used, through the creation of categories that investigated drought coverage from different agents such as sources and response agents, as well as the proposed solutions. As a result, it was possible to visualize coverage that cites emergency solutions and responses, without pointing out the implementation details, evidence, as well as the limitations of the response. We also visualized an uncritical coverage predominantly in relation to the drought phenomenon, through a generalization of the place, as well as blaming the climate, which led us to reflect on how this coverage could be done from the journalism of solutions and with a preventive aspect of approach.